A longitudinal investigation of work environment stressors on the performance and wellbeing of office workers. (January 2016) - Lamb, S.; Kwok, K.C.S.
Abstract: This study uses a longitudinal within-subjects design to investigate the effects of inadequate Indoor Environmental Quality (IEQ) on work performance and wellbeing in a sample of 114 office workers over a period of 8 months. Participants completed a total of 2261 online surveys measuring perceived thermal comfort, lighting comfort and noise annoyance, measures of work performance, and individual state factors underlying performance and wellbeing. Characterising inadequate aspects of IEQ as environmental stressors, these stress factors can significantly reduce self-reported work performance and objectively measured cognitive performance by between 2.4% and 5.8% in most situations, and by up to 14.8% in rare cases. Environmental stressors act indirectly on work performance by reducing state variables, motivation, tiredness, and distractibility, which support high-functioning work performance. Exposure to environmental stress appears to erode individuals' resilience, or ability to cope with additional task demands. These results indicate that environmental stress reduces not only the cognitive capacity for work, but the rate of work (i.e. by reducing motivation). Increasing the number of individual stress factors is associated with a near linear reduction in work performance indicating that environmental stress factors are additive, not multiplicative. Environmental stressors reduce occupant wellbeing (mood, headaches, and feeling 'off') causing indirect reductions in work performance. Improving IEQ will likely produce small but pervasive increases in productivity. Highlights: We measure responses to indoor environmental quality in real office workers. Environmental stress reduces work performance by 2.4–5.8% in most situations. Stressors reduce motivation, and increased tiredness and distractibility. Stressors reduce not only cognitive performance, but the rate of work. Stress factors appear to be additive, not multiplicative.